ANALYSIS OF THE LEGAL BASIS FOR THE FULFILLMENT OF CUSTOMARY DEFAULT SANCTIONS (Contract Agreement) - Uti Abdulloh (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to examine more deeply the fulfillment of default sanctions through customary law from a positive legal aspect. This is intended to get a clear picture of how the sanctions of default are applied through customary law and views in posisitf law. This research is a type of doctrinal normative research (doctrinal reseach), the selection of the type is based on several understandings and opinions of the author, This research uses a legal comparative approach, a conceptual approach (conceptual approach), and a case approach (case aproach).A comparative approach to legislation is also very necessary because as a legal country that adheres to the Civi law system,  laws are the main source of law (rule based). A comparison of laws was carried out by examining all laws and related regulations in this study. This study explains that customary law has an important role in the arrangement of treaty contracts in indigenous peoples of Indonesia. As a cultural heritage recognized in the 1945 Constitution, customary law provides a basis for the implementation of agreements, especially those carried out orally based on mutual trust. Principles such as freedom of contract, consensualism, legal certainty, and good faith are important foundations for the validity of contracts in customary and national law.